2012
DOI: 10.1097/bsd.0b013e31820bb20f
|View full text |Cite
|
Sign up to set email alerts
|

Combined Posterior and Delayed Staged Mini-open Anterior Short-segment Fusion for Thoracolumbar Burst Fractures

Abstract: This combined procedure is less invasive than the conventional combined one, and finally achieves shorter stabilization, resulting in preservation of motion segments. It thus seems to be a reasonable treatment option for thoracolumbar burst fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…failure of the anterior and middle column under compression or disruption of the posterior column) or associated with a neurologic deficit are most often treated surgically (Verlaan et al 2004, Oner et al 2010). Currently, short-segment posterior stabilization is considered to be the first step towards preserving motion segments, preventing adjacent segment disease, shortening operating time, and reducing intraoperative blood loss (Verlaan et al 2004, Dai et al 2007, Zdeblick et al 2009, Gelb et al 2010, Kim et al 2011, Schmid et al 2011, Tofuku et al 2012). Furthermore, short-segment posterior stabilization can be performed in a standard emergency surgery setting.…”
mentioning
confidence: 99%
“…failure of the anterior and middle column under compression or disruption of the posterior column) or associated with a neurologic deficit are most often treated surgically (Verlaan et al 2004, Oner et al 2010). Currently, short-segment posterior stabilization is considered to be the first step towards preserving motion segments, preventing adjacent segment disease, shortening operating time, and reducing intraoperative blood loss (Verlaan et al 2004, Dai et al 2007, Zdeblick et al 2009, Gelb et al 2010, Kim et al 2011, Schmid et al 2011, Tofuku et al 2012). Furthermore, short-segment posterior stabilization can be performed in a standard emergency surgery setting.…”
mentioning
confidence: 99%
“…In study by Carl et al [36], an average blood loss of 2300 ml and an average of a 4-day delay until surgery after the accident were reported. However, Tofuku et al [37] reported an average blood loss of 545 ml in combined delayed staged anterior surgery. In the present study, the average blood loss was 516 ml in combined delayed staged anterior surgery, which was more favorable and less invasive than the conventional one-stage combined procedure, and also comparable with that of Tofuku et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we used single-stage posterior corpectomy, interbody fusion with titanium mesh and transpedicle screw fixation for this type of injury. This approach combines the advantages of the anterior only approach and the posterior only approach and reduces the trauma and complications that may arise with the combined approach ( 13 , 14 ); however, this approach is not suitable for patients with severe osteoporosis or those in poor physical condition. Nonetheless, this method allows for the completion of decompression, reduction, fusion and fixation in one stage and has the following advantages: less trauma, shorter operative time, less blood loss and total decompression.…”
Section: Discussionmentioning
confidence: 99%